Apakah Asing Memberikan Nilai Tambah Pada Industri Keuangan Di Indonesia? - Lily Leonita (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of the paper is to study of value created by foreign shareholders in Indonesia banking over the period 2011-2016. We analysed the value creation by foreign shareholders by comparing the key financial performance. We analysed 7 micro key financial ratios (profitability, efficiency, growth, firm size, liquidity, solvency and asset quality). We used parametric panel data dummy regression. The empirical results show that banking owned by foreign shareholders gave value to profit margin and growth of revenue and asset. The research also found that foreign shareholders were better in managing liquidity ratio such as loan to deposit.